2008
DOI: 10.1016/s0973-0508(08)80004-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of traumatic extradural haematoma: Experiences with 610 patients and prospective analysis

Abstract: This study was carried out to find out the age, sex, mode of injury, localization, clinical presentation, CT findings, operative measures and outcome of extradural haematoma in the patient population at Dhaka Medical College. 610 consecutive patients with cranial extradural haematoma who underwent surgery in department of Neurosurgery from 1st January 2006 to 6th October 2008 were included in this prospective study. Each of the patients were evaluated in term of age, sex, mode of injury, localization of haemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 33 publications
7
32
3
1
Order By: Relevance
“…There is strong evidence that gender does not affect the prognosis in TBI [6,10,11]. In our study, gender was not placed among the factors which were significantly associated with the outcome after 6 months.…”
Section: Demographic Datacontrasting
confidence: 57%
See 1 more Smart Citation
“…There is strong evidence that gender does not affect the prognosis in TBI [6,10,11]. In our study, gender was not placed among the factors which were significantly associated with the outcome after 6 months.…”
Section: Demographic Datacontrasting
confidence: 57%
“…They came to similar conclusions [15,39]. Khaled et al investigated patients with EDH, and stated that the time between a trauma and a surgery is the most important prognostic factor, and shortening this time to a minimum can reduce mortality to zero [11]. Seelig et al based their study on patients undergoing surgery for SDH, and found that the surgery would reduce mortality from 90% to 30% within 4 h [40].…”
Section: Time Injury-operationmentioning
confidence: 79%
“…Bagaimanapun juga kejadian koma di antara pasien trauma lebih tinggi, yaitu sekitar 9% sampai 15%. 5 Hematoma epidural paling sering terjadi pada orang muda yang disebabkan karena kecelakaan lalu lintas (KLL). Pada dewasa muda insiden tertinggi terjadi pada kelompok umur 20-30 tahun, dan jarang terjadi pada umur di atas 60 tahun, hal ini disebabkan pada usia tua secara anatomis terdapat perlekatan antara duramater dan kranium.…”
Section: Pendahuluanunclassified
“…According to Bullock et al, 21 patients who had EDH with thickness >15 mm, midline shift >5 mm should be surgically managed regardless of GCS score, and craniotomy provides a more complete evacuation of hematoma. Khaled et al 22 also found in their study that surgical intervention in EDH is associated with the best prog nosis. Out of many factors affecting the outcome, the most important one is the duration of time between accident and surgery; mortality can be close to 0% if this time interval can be minimized.…”
Section: Discussionmentioning
confidence: 83%